Which component of sulphasalazine is active in rheumatoid arthritis?. Issue 6481 (25th May 1985) - Pullar, T; Hunter, J A; Capell, H A
Abstract : Sulphasalazine is known to be effective as a second line agent in the treatment of rheumatoid arthritis. The two chemical constituents of sulphasalazine (sulphapyridine and 5-aminosalicylic acid) were assessed separately in the treatment of rheumatoid arthritis. Over 24 weeks sulphapyridine showed a pronounced second line effect comparable with sulphasalazine and with a similar toxicity profile, whereas 5-aminosalicylic acid showed only a weak first line effect. Thus sulphapyridine appears to be the active moiety responsible for the second line effect of sulphasalazine in rheumatoid arthritis. The efficacy of the antibacterial component of sulphasalazine yet again permits speculation about the role of a bacterial pathogen in the aetiopathogenesis of rheumatoid disease.